The Economic Issues of Compulsory Health Insurance: Reply - Campbell, Rita Ricardo; Campbell, W. Glenn (Quarterly Journal of Economics, 1953)
Journal Article The Economic Issues of Compulsory Health Insurance: Reply Get access Rita Ricardo Campbell, Rita Ricardo Campbell Washington, D. C. Search for other works by this author on: Oxford Academic Google Scholar W. Glenn Campbell W. Glenn Campbell Washington, D. C. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 67, Issue 1, February 1953, Pages 125–135, https://doi.org/10.2307/1884152 Published: 01 February 1953